Pelatihan Penggunaan Google Form untuk Alat Pembelajaran Bagi Guru SDN 111/I Muara Bulian - Arsil Arsil; Muhammad Sholeh; Silvina Noviyanti; Alirmansyah Alirmansyah (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to determine the combined dose of mustard greens based on the optimal dose of NPK inorganic fertilizer and rabbit urine organic fertilizer that could increase the growth and yield of mustard greens (Brassica juncea L.). This study used an experimental method with a single factor Randomized Block Design (RAK) consisting of a combination of NPK and rabbit urine with 11 treatments repeated 3 times so that 33 experimental units were obtained and then analyzed using the DMRT test level 5%. The parameters analyzed were plant height (cm), number of leaves (sheet/plant), leaf length (cm), leaf area (cm2), plant weight (grams/plant), plant weight suitable for consumption (grams/plant), and plant weight per plot (grams/plant). The results showed that the combination treatment of NPK and rabbit urine had no significant effect on plant height, number of leaves and leaf length. The results of treatment H (NPK fertilizer 150 kg/ha rabbit urine 20 lt/ha) gave the highest leaf area of ​​266.36 cm2, the highest plant space weight was 192.00 grams/plant, fresh weight of plants suitable for consumption was 182.15 grams/plant. plants and the highest plant weight per plot was 1796.67 grams/plot.